1989
DOI: 10.1002/ijc.2910430225
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment and activation of tumor‐specific immune t cells in situ: Functional studies using a sponge matrix model

Abstract: The activation of tumor-specific precursor cytotoxic T lymphocytes (CTLP) into cytotoxic T cells (CTL) was demonstrated in situ using the well-defined, highly metastatic ESb tumor as murine model system. Ten days after optimal immunization of syngeneic mice with a sublethal dose of live ESb tumor cells in the pinna, tumor-sensitized non-cytotoxic CTLP were recovered from the spleen and lymph nodes. These cells mature into tumor-specific CTL upon restimulation in vitro. Using a confined sponge matrix compartmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…It would be of interest to identify, first, the different cytokines produced in the wound fluid of PVA foam‐treated patients, compared with patients without foams, and secondly, to determine which cytokines are produced in vitro by the foam T cells after bacterial stimulation. Finally, different animal models have shown that T cell infiltration inside the sponge matrices can be manipulated by prior injection of antigens and/or various cytokines [16,27–30]. Thus, PVA foams could be redesigned to improve T‐cell infiltration and T‐cell activation, for example by coating the foams with co‐stimulatory substances or by soaking them in T cell‐attracting chemokines before implantation.…”
Section: Discussionmentioning
confidence: 99%
“…It would be of interest to identify, first, the different cytokines produced in the wound fluid of PVA foam‐treated patients, compared with patients without foams, and secondly, to determine which cytokines are produced in vitro by the foam T cells after bacterial stimulation. Finally, different animal models have shown that T cell infiltration inside the sponge matrices can be manipulated by prior injection of antigens and/or various cytokines [16,27–30]. Thus, PVA foams could be redesigned to improve T‐cell infiltration and T‐cell activation, for example by coating the foams with co‐stimulatory substances or by soaking them in T cell‐attracting chemokines before implantation.…”
Section: Discussionmentioning
confidence: 99%
“…These cells appear to be of importance for protective immunity because of the following: (a) in our early studies we could show that the specificity of in vitro generated CTL was similar to that of protective immunity in vivo [8]; (b) some in vitro generated CTL clones could transfer protective immunity in a Winn-type assay (unpublished observations); (c) in sponge-matrix studies we demonstrated that in situ activated cytolytic CD8 + T cells from the sponges were able to transfer systemic protective immunity against ESb tumour cells [36]. In this report we show that a similar tumour-specific cytolytic T cell response can be activated not only in an artificial sponge but also in a physiological compartment such as the peritoneal cavity.…”
Section: Discussionmentioning
confidence: 83%
“…These CTL proliferate and infiltrate the tumour burdenl This implies an increase of the effector T cell concentration at the tumour site (see e.g. Zangemeister-Wittke et al, 1989). The immune response is also accompanied by an increase of the T cell specificity (Moscovitch et al, 1986).…”
Section: Stabilization Of Tumoural States Due To Increased Effector-tmentioning
confidence: 99%